Social capital has a voice: Theory, method and practice,"capturing the voice' - Whiteley, Alma; Gilhespy, H. (Rattana Bundit University, 2011)
This paper is Thai oriented and presents theories, methods and practices to capture the voice of managers and employees who, separately and together, make up the organizational voice, its social capital. Thailand has escalated its efforts to become more competitive but at the same time, blend such efforts with the National Economic and Social Development Plan (NESDP), the sufficiency economy principle and, in a foundational way, the important Buddhist values that permeate business as well as social life. The paper poses, as seeks to answer the following questions.Why should employees be given a voice? Traditionally, they have been there to be managed by managers and leaders who reflect the vision, mission and strategy of the organization. Employees as valued social capital in the west are now well recognized and, increasingly, research has been conducted to investigate employees’ perceptions about motivation and commitment. However, as found, there are conflicting cultural imperatives between western and Thai culture. This paper will use Thai government and business initiatives to answer the question of why employees’ voices are necessary for success. The next question asks “Which theories inform research into engaging with the workforce to capture the employee voice – and what do managers and leaders need to know”? The theories discussed in this section are selected from the ‘family’ of theories that inform how to gather and use employees’ perceptions – Symbolic interactionism, phenomenology ethnomethodology and ethnography, highlighting symbolic interactionism and phenomenology, using data from our researches to illustrate the appropriate questions asked of each. Grounded theory/grounded research demonstrates a useful method of capturing employees’ voices.